Recycling of lithium-ion batteries: a brief review of processes, advancements, and prospects - Moreira, Yago Henrique Barbosa; Mantegazini, Diunay Zuliani; Andrade, George Ricardo Santana; Bacelos, Marcelo Silveira (Brazilian Journal of Production Engineering, 2024)
This work presents a brief review of conventional (pyrometallurgy and hydrometallurgy) and alternative recycling processes of LIBs (direct recycling, bio-metallurgy, electric field, and thermal induction), which are responsible for recovering valuable materials such as Li, Ni, Co, Mn, Cu, Al and graphite. Bibliographic and documental research was used to state comparisons between different technologies. Research findings reveal that alternative recycling is more efficient and sustainable when compared to conventional methods. However, the commercial use of conventional processes persists due to their established technologies and large-scale production infrastructure. Therefore, overcoming technological bottlenecks associated with alternative recycling will support the lithium battery (LIB) production chain, meeting the growing demand in the electric vehicle market. Technological challenges need to foster the development of innovative and sustainable recycling technologies for lithium batteries in line with solid waste management policies.